Role of B lymphocyte ratio in development of type 2 diabetes mellitus: results of a 7-year follow-up study - Shen, Dan-Ting; Qie, Zhong-Hong; Zhao, Lan-Jing; Pan, Li-Juan; Wang, Su-Dan; Liu, Chun-Xing (Frontiers in Endocrinology, 2025)
ObjectiveTo investigate the association between B lymphocyte ratio (BLR) and type 2 diabetes mellitus (T2DM) outcome among healthy people.MethodsA retrospective study cohort was constructed based on healthy people who participated in annual physical examination in Shanghai Health and Medical Center from 2013 to 2020. For each patient, we collected data at the first physical examination in 2013. The Cox proportional risk regression model was used to analyze the association between BLR and the risk of T2DM. The mediating effect of traditional metabolic factors were further explored.ResultsThe study included 1505 participants with a mean age of 48.77 ± 8.33 years at baseline and a follow-up duration of 7.36 ± 0.99 years. During follow-up, a total of 72 new T2DM cases were identified (7.9/1000 person-years). After adjusted for confounders, the results showed that the participants with higher level of BLR (Quartile 4) had a doubling of the risk of T2DM when compared to those with lower BLR level (Quartile 1). The association of BLR with the risk of T2DM remained robust when patients with hypertension or patients with obesity were excluded. In addition, traditional metabolic factors including HDL-C and LDL-C partially mediated the association between BLR and the risk of T2DM.ConclusionElevated BLR level is significantly associated with a higher risk of T2DM development. HDL-C and LDL-C partially mediated the association between BLR and T2DM risk. Our research may have the potential to provide new therapeutic targets for the treatment of T2DM.